Respon Perilaku Kupu–Kupu pada Kanopi Bercelah dan Kanopi Tertutup di Hutan PPKA Bodogol, Taman Nasional Gunung Gede Pangrango - Wijaya, Riko Pandu; Diana, Putri; Anggraeni, Septiana; Kusyaifah, Efah; Amalia, Nurul (Bioma, 2014)
Abstract Tropical forest vegetation varies with vegetation structure. Branch characteristics were very complex, created gaps with some variation.Gaps can form physical environment that affect the performance of motion, flight and thermoregulation of insects. The purpose of this study was to determine the behavioral response of butterflies to patch influenced by canopy covering of a tropical rain forest rain. The study was conducted on 20-22 June 2013, in 6 pairs of patch on the vegetation canopy gaps and closed canopy PPKA Bodogol, Sukabumi, West Java. Behavioral observations used was focal animal sampling technique and analyzed by Manova Test. Results showed that the location and species in both patch significantly affect the behavior of butterflies. Key words: behavioural respons, butterfly , canopy gaps , closed canopy